Year Round. Method of speech development and correction - Pavlova, Y.B.; Khotyleva, T.Y. (Autizm i narušenie razvitiâ, 2016)
This methodological manual is created based on the analysis of many years of experience of teachers working with children with developmental disorders. The manual is aimed at pre-school children or first graders with speech and communication difficulties leading to academic failure. Методическое пособие создано на анализе многолетнего опыта работы педагогов с детьми, имеющими нарушения в развитии, и предназначено для подготовки к школе детей или для первоклассников, име¬ющих речевые проблемы и трудности в общении, что приводит к школьной неуспешности.